PARTISIPASI MASYARAKAT DALAM MENDUKUNG DESA WISATA EKOLOGIS DI DESA NYAMBU, KECAMATAN KEDIRI, KABUPATEN TABANAN - Putu Agus Suantara; Ida Bagus Made Parsa; Ni G.A. Diah Ambarwati Kardinal (UNHI Press, 2019)
Nyambu Village is a Tourism Village that takes the ecological concept (Ecotourism), The beauty of natural scenery and culture makes Nyambu Village has the attraction to be visited by tourists. Nyambu village atmosphere with all its contents is the perfect big potential with the unification of nature and culture which is the strong character of Nyambu Village itself. This study describes how community participation in supporting Ecological Tourism Village in Nyambu Village, Kediri Sub-district, Tabanan District, and describes the form of community participation, the level of community participation in planning, implementation, utilization, evaluation, business opportunity and identifying factors influence public participation through age, sex, education and employment. This research is a qualitative research using deductive approach, with data collection methods obtained from field observation, interview and secondary data from related offices while interviews and questionnaires conducted by the method of puposive sampling. There are four forms of participation in Nyambu Village, among others, the participation of money, the participation of material or matter, the participation of personnel, the participation of the mind, and the level of participation in the planning, implementation, utilization, evaluation and business opportunities are very good. while the involvement or participation of Nyambu Village community on village tourism activities that took place in Nyambu Village Kediri District, Tabanan Regency seen from the factor of participation is the age factor of 17- 28 years old with high school education.